1996
DOI: 10.1002/1529-0131(199608)9:4<302::aid-anr1790090415>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

The use of trained patient educators with rheumatoid arthritis to teach medical students

Abstract: To assess whether patients with rheumatoid arthritis IRA) trained as educators can enhance the integration of clinical and basic science education among second-year medical students during their rheumatology sequence. Methods. Twenty patients with RA and strong communication skills were extensively trained to teach students how to pe$orm the whole-body joint examination. Each arthritis educator taught three 2-hour small group sessions and participated in a concluding2-hour panel discussion with the entire clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 6 publications
3
45
0
Order By: Relevance
“…Moreover, as previously shown (11,12) and as noted here, arthritis educators are well accepted by physicians-in-training. Finally, the results of this study provide evidence that the significant improvement noted after the arthritis educator intervention persists for at least two weeks.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Moreover, as previously shown (11,12) and as noted here, arthritis educators are well accepted by physicians-in-training. Finally, the results of this study provide evidence that the significant improvement noted after the arthritis educator intervention persists for at least two weeks.…”
Section: Discussionsupporting
confidence: 82%
“…The details of this examination have been previously reported (12). Five of the 12 questions addressed information about arthritis, 5 questions addressed confidence to carry out a musculoskeletal examination, and 2 questions addressed attitude about the impact of arthritis.…”
Section: Methodsmentioning
confidence: 99%
“…One variation on the SP is the patient educator, who has actual disease and can demonstrate abnormal pathology on him/herself. Patient educators with rheumatoid arthritis have been well studied in the musculoskeletal literature and are particularly effective in educating students about the psychosocial aspects of arthritis and chronic musculoskeletal pain/limitation [46]. Additionally, patient educators have been shown to be at least as effective as physicians in teaching physical exam skills [47][48][49].…”
Section: Educational Strategies and Implementationmentioning
confidence: 99%
“…Previous qualitative research on MSK teaching, and specifically on PP Õ IA patient educators, has primarily been limited to reports of participants' experiences (Gruppen et al 1996;Bell et al 1997;Hendry et al 1999). This study is the first to compare patient educators to physician tutor teaching by directly observing and analysing the teaching sessions through a collective case study approach.…”
Section: Discussionmentioning
confidence: 99%
“…open-ended questions by students on their experience of patient educator teaching found that students enjoyed the chance to see real patients and felt they had a better understanding of the impact of arthritis on patients' lives. They also felt that the patient educators had good ability to explain how to do an MSK exam (Gruppen et al 1996). In a final study's description of written responses to open-ended questions, students suggested that exposure to MSK patient educators ''increased their empathy with the arthritis sufferer and improved their awareness of the disability resulting from arthritis''; however, students also indicated that they believed that rheumatology fellows were more likely to teach ''correct'' techniques (Smith et al 2000).…”
Section: Practice Pointsmentioning
confidence: 99%